Novel computational tool for efficient structural analyses of geothermal wells. (May 2021) - Hoang, Nguyen-Hieu; Mainçon, Philippe; Philippe, David; Coudert, Terence; Bjørset, Arve; Sæther, Sturla
Highlights: A novel tool Casinteg was developed for efficient geothermal well analyses. Casing creep and plasticity behaviours are important for geothermal well designs. Excellent agreement between Casinteg and Abaqus models was obtained. Casinteg was used to analyse global structure behaviour of IDDP-1 well. Efficiency and flexibility of Casinteg are assets for casing system design. Abstract: In geothermal energy, a huge energy potential lies in hydrothermal reservoirs close to magma where ultra-high temperature fluids (>450 ° C) can be harnessed. Well casing system needs to be properly designed to ensure its integrity during its service lifetime. There currently exist neither any commonly accepted design tools nor standards regulating geothermal well design under such conditions. In this study a novel tool, Casinteg, was developed for structural analyses of geothermal wells. The tool is intended to bridge the gap between simplified analytic solutions and complex FE-based commercial software. The reliability and efficiency of the constitutive models implemented in Casinteg were verified in comparison with Abaqus. Casinteg's capability for structural analyses of full geothermal wells was preliminarily investigated, using IDDP-1 well as a case study. The calculated stress in the production casing was in a good agreement between Casinteg and Ansys models, while the computational time of Casinteg simulations was within minutes. Further developments are still needed. However, preliminary results were encouraging and have demonstrated the benefit of Casinteg for efficient structural analyses of full geothermal wells.